Gugon Tuwon dalam Perspektif Masyarakat Bali - Sutarini, Ni Luh Putu (Dharma Sastra : Jurnal Penelitian Bahasa dan Sastra Daerah, 2024)
Gugon tuwon is a piece of advice left by ancestors passed down to children and grandchildren, containing teachings to ensure life continues well. The existence of gugon tuwon in Balinese society today is no longer a teaching or advice in living life. Reflecting on this, there is an important meaning that can be learned from gugon tuwon, in fact it is the principle of believing in what is worthy of belief, trusting in the true. The meaning of gugon tuwon today tends to be related to several aspects, namely, sraddha, responsibility, and Balinese ajeg. Traditions use gugon tuwon as a fact that is difficult to explain logically, but difficult to deny. No one blames Gugon tuwon, and no one doubts how Hindus' belief when carrying out a ritual ceremony, even if it is only based on tradition passed down from generation to generation, without knowing the philosophy, does not only mean being confident but also carrying it out seriously. Basically, gugon tuwon is a response to the younger generation to have a good attitude in everyday behavior